PENGUJIAN KAUSALITAS ANTARA VARIABEL MAKROEKONOMI DENGAN RETURN PASAR DI BURSA EFEK INDONESIA : SEBUAH PENDEKATAN VECTOR AUTO - Anggi Hapsari Nurullita (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2011)
Indicators of macroeconomic have major impact on capital markets in general and stocks in particular. Influence of these indicators can be positive or negative. Vector Auto Regression (VAR) is a method of analysis used to predict the time series variable and analyze the dynamic impact factor interference in a system variable. VAR analysis is very useful to assess the linkages between economic variables. This research aims to see the influence of iIndicators of macroeconomic such as the exchange rate (EXCHANGE), interest rate Bank Central of Indonesia Certificates (SBI) and rate of inflation (INFLATION) to market return (REIHSG) in Indonesian Stock Exchange in the period 2004:1-2011:10. Data obtained from the Monthly Stock Price Index Statistics JSX. This research appllying several stages of testing as follows: unit root test, the optimal lag test, Granger causality test and Vector Auto Regression model (VAR). The results of unit root test in this study suggests that the data used for processing in the first degree and VAR Granger test because only the stationary stock index return variable in zero degree (level). On the test results suggested the optimal lag is the lag 3. On the Granger causality test is known that the Granger test variable rate (EXCHANGE) has a one-way impact or the exchange rate (EXCHANGE) affect market return (REIHSG) interest rate of Bank Central of Indonesia Certificates (SBI) and the rate of inflation (INFLATION) has a two direction or impact mutual Causality. These results indicate that there is a weak Granger causality between interest rates Bank Central of Indonesia Certificates (SBI) and rate of inflation (INFLATION) to market return (REIHSG).Keywords: Vector Auto Regressive (VAR), Macroeconomic, Granger Causality, IHSG stock return